TINGKAT LITERASI INFORMASI MAHASISWA SKRIPSI JURUSAN PENDIDIKAN MATEMATIKA - Aan Subhan Pamungkas (Universitas Islam Nusantara, 2016)
The development of technology and communication is currently growing rapidly, thus impacting the largenumber of circulating information. The amount of information that is available now makes findinginformation difficult, so it takes the ability to search, choose and evaluate which information is needed. Theability to search, choose and evaluate information better known as information literacy is an ability that mustbe owned by the community to realize an information society. Students are part of the community who playa role in filling development, of course must have this ability as a basic ability. With information literacy thatis capable of helping students achieve optimal academic abilities and support student self regulated learning.Especially students who are completing their thesis to get an academic degree, this ability is very supportiveof students when looking for relevant sources or references that support the research topic. This researchwas carried out in the 2015/2016 academic year with the research subjects being 70 students who contractedthesis, consisting of 17 male students and 53 female students. The instrument used is an information literacyquestionnaire adapted from Nurtiar (2012). Based on the results of data analysis, it was obtained a picturethat the average level of information literacy of thesis students in the Department of Mathematics EducationUntirta amounted to 40.17 included in the less category. This indicates that students are aware of the needto get the information needed, and have knowledge about matters relating to the search and use ofinformation even though there are still few. So that it requires guidance and intensive information literacytraining that is integrated in one subject